1999
DOI: 10.1161/01.str.30.8.1632
|View full text |Cite
|
Sign up to set email alerts
|

Marfan Syndrome Is Not Associated With Intracranial Aneurysms

Abstract: Background and Purpose-It has been proposed that patients with Marfan syndrome have an increased prevalence of intracranial aneurysms. This proposition is based on 10 clinical reports, 1 pathology case, and an autopsy series of 7 patients. By contrast, 5 clinical series of Marfan patients have failed to document any such relationship. We present our institution's autopsy and clinical experience with Marfan syndrome and analyze in our patient population the purported association between this condition and intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
2
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 25 publications
1
41
2
4
Order By: Relevance
“…In a postmortem series of 25 patients with Marfan syndrome, Conway et al 1 found an aneurysm prevalence of just 4%. In addition, in a series of 129 patients with Marfan syndrome, van den Berg et al 2 found no patients who presented with a symptomatic intracranial aneurysm.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In a postmortem series of 25 patients with Marfan syndrome, Conway et al 1 found an aneurysm prevalence of just 4%. In addition, in a series of 129 patients with Marfan syndrome, van den Berg et al 2 found no patients who presented with a symptomatic intracranial aneurysm.…”
Section: Discussionmentioning
confidence: 97%
“…Early studies suggesting an association between Marfan syndrome and intracranial aneurysms were limited to small case series and case reports. 1 However, larger studies have since suggested that there is no association between aneurysms and Marfan syndrome. [1][2][3] Nonetheless, the association is still widely cited in the literature.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent studies, however, cast doubt on the supposed association between cerebral aneurysm and Marfan syndrome. 22,23 No investigation of the prevalence and nature of neurovascular complications has been performed in a large group of patients. We therefore undertook a retrospective, hospital-based study of Marfan patients followed in the specialized Marfan clinic or admitted to the Johns Hopkins Hospital (JHH) over an 8-year period to assess the frequency, presentation, and etiology of neurovascular complications this disorder.…”
mentioning
confidence: 99%
“…Wityk et al, noting that most strokes are cardioembolic, cast doubt on the association between spontaneous, isolated internal carotid artery dissection and MFS. Other two studies raised a similar question of whether there is truly an association of intracranial aneurysm with MFS (Conway et al, 1999;van den Berg et al, 1996). The skeletal manifestations include tall stature, pectus excavatum, or carinatum, higharched palate, arachnodactyly, laxity of ligaments with scoliosis, or joint hyperextensibility (Pyeritz, 2000).…”
Section: Marfan Syndromementioning
confidence: 99%